Clinical profile of renal diseases in children in tertiary care centre - Agrawal, Jyoti; Chaudhary, Shipra; Shrestha, Manju (Birat Journal of Health Sciences, 2022)
Introduction: Renal diseases in children and young adult can be difficult to diagnose early as it may present only with few symptoms, tends to have different course than adult and respond variously to different treatment. The pattern of renal disease in children is different from developing countries as compared to developed countries. Objective: To know the current profile and aetiology of renal disease in children Methodology: This is a hospital based prospective observational study carried from March, 2014 to February 2015 at BPKIHS. Patients with renal disease, both inpatient and outpatient from birth to 14 years of age were enrolled in the study. The diagnosis of renal disease was be made on clinical and laboratory criteria. Results: Total of 120 patients were enrolled in our study which contributed to 3.74% of total admission. The commonest feature of presentation was edema (75%) , followed by fever (65%), hypertension (60%), decreased urine output (45%) and hematuria (25%) . Most common diagnosis was acute glomerulonephritis (40%) followed by Nephrotic syndrome (25%) and UTI (25%). Renal biopsy was done for 10% of cases and most of them were steroid dependant nephrotic syndrome. 5% of our cases expired because of MODS, sepsis and AKI. Conclusion: Renal disease contributes to a large part of hospital pediatric admission as well as mortality and morbidity to the children. There is scanty data and need for detailed study on specific renal disease is of great need to plan optimal renal care for these children.